Photo- and electro-chemical strategies for indazole synthesis - Binbin Huang (Tetrahedron Chem)
The indazole core is prevalently found in the structures of bioactive molecules, demonstrating promising potential in medicinal chemistry and drug discovery, which therefore has attracted sustained attention from the synthetic community. Over the recent decades, significant progress has been achieved in both organic photocatalysis and electrosynthesis, offering novel approaches for the efficient and sustainable synthesis of various functionalized indazoles. This mini-review highlights the emerging methodological advancements in photo-/electro-chemical synthesis of two common forms of indazole, namely 1H- and 2H-indazoles, which are classified by specific intramolecular bond formation patterns: (1) C–C bond formation, (2) C–N bond formation, and (3) N–N bond formation. The reaction conditions, representative scopes, and mechanistic understandings of these protocols are emphasized, to elucidate the advantages and limitations in current strategies, with an aim to inspire future innovations that may address challenges in modern indazole synthesis.